2005
DOI: 10.1590/s1135-57272005000500004
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de los ingresos urgentes innecesarios sobre las estancias hospitalarias en un hospital de Asturias

Abstract: RESUMENFundamento: Los ingresos innecesarios en los hospitales de agudos tienen importantes consecuencias sobre su eficiencia y organización. El objetivo de este estudio es identificar el grado de inadecuación de los ingresos realizados desde un servicio de urgencias hospitalario y sus causas, así como cuantificar las estancias inadecuadas generadas por estos ingresos.Método: Se evaluó la adecuación de 622 ingresos realizados en al año 2002 seleccionados aleatoriamente, y la del total de estancias generadas po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…The AEP has had various applications, usually corresponding to inappropriateness studies in specific clinical services. [11][12][13][14][15][16][17] Only a few studies have been conducted on the hospital as a whole. 18,19,21 The various studies use different sampling strategies, which may be related to the study design (retrospective or concurrent) or to the sample unit.…”
Section: Discussion the Appropriateness Evaluation Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The AEP has had various applications, usually corresponding to inappropriateness studies in specific clinical services. [11][12][13][14][15][16][17] Only a few studies have been conducted on the hospital as a whole. 18,19,21 The various studies use different sampling strategies, which may be related to the study design (retrospective or concurrent) or to the sample unit.…”
Section: Discussion the Appropriateness Evaluation Protocolmentioning
confidence: 99%
“…The AEP has had various applications, usually corresponding to appropriateness studies of specific clinical services such as emergency, medical services, or surgery. [11][12][13][14][15][16][17] Only a few studies have examined the impact of inappropriate admissions and stays on an acute care hospital as a whole. 18,19 The factors traditionally associated with a higher rate of inappropriateness are old age, medical as opposed to surgical services, and prolonged stays.…”
mentioning
confidence: 99%
“…Un aspecto que debe considerarse son las limitaciones inherentes a la utilización del AEP, que son comunes a todos los trabajos que manejan esta herramienta. Por un lado, el AEP no cuestiona si los procedimientos diagnósticos y terapéuticos prestados al paciente hospitalizado están o no indicados, sino que se asume siempre que éstos son adecuados y están correctamente indicados desde el punto de vista clínico, evaluándose exclusivamente el nivel asistencial en el que se prestan, así como el momento y la oportunidad de la prestación, lo que sin duda podría infravalorar la inadecuación 2,14,15 . Asimismo, el hecho de que el cuestionario se elaborara hace 25 años implica que algunos de los supuestos que justifican una estancia podrían haber quedado obsoletos en la actualidad 7 .…”
Section: Discussionunclassified
“…It is more common in surgery departments. Velasco’s [15] study illustrated that patients who were not properly admitted had three times the length of hospital stay compared to those admitted appropriately. Eriksen [16] has measured the proportion of inappropriate admission of internal medicine and the cost, and the findings suggested that not accepting inappropriate admission did not bring the hospital the same percentage of cost reduction.…”
Section: Introductionmentioning
confidence: 99%